The bacterial species associated with aspirated foreign bodies in children. Issue 3 (June 2018) - Gruber, Maayan; van Der Meer, Graeme; Ling, Benjamin; Barber, Colin; Mills, Nikki; Neeff, Michel; Salkeld, Lesley; Mahadevan, Murali
Abstract: Objective: Inhaled foreign bodies in children are common and may be complicated by secondary airway tract infection. The inhaled foreign body may act as carrier of infectious material and the aim of this study was to explore the bacterial species associated with aspirated foreign bodies in a cohort of children. Methods: Retrospective case series of 34 patients who underwent rigid laryngobronchoscopy because of foreign body aspiration. Each patient had a sample taken from tracheobronchial secretions during the procedure. Results: The average patient age was 31.2 months and the average hospital stay was 2.5 days. Of the foreign bodies 24 (71%) were organic in nature and 10 (29%) were non-organic. Twenty eight (82.3%) patients had mixed oropharyngeal flora organisms growth. Fifteen (44%) samples were positive for organisms other than oropharyngeal flora with the most common cultured organisms being: Streptococcus pneumonia (4/12%), Haemophilus influenza (4/12%), Moraxella catarrhalis (4/12%). Four samples (12%) grew a fungus; Candida albicans was cultured in 3 patients and Aspergillus glaucus was identified in one sample. Of the non-oropharyngeal organisms 7(47%) demonstrated antibiotic resistance with four having resistance to amoxycillin, two resistant to penicillin and one resistant to cotrimoxazole. Conclusion: Some children who present with aspirated foreign body may be complicated with secondary airway infection. Antibacterial treatment might be considered in some of these cases. The regimen of antibiotics should aim to cover oropharyngeal flora, S. pneumonia, H. influenza and Moraxella catarrhalis.